GENERATION-BASED CAREER DEVELOPMENT PATHWAYS: AN EFFORT TO OPTIMIZE THE PERFORMANCE OF GEN-Z EDUCATORS - Sabilil Muttaqin; Muhfidatul Nafila; Nofi Maria Krisnawati; Yazid Hady; Fatkhul Mubin; Putra Dian Kharisma Ivada (Hikmah: Journal of Islamic Studies, 2026)
AbstractGeneration Zs, often labeled as "digital natives," are now increasingly joining the education sphere. This generation has unique characteristics, such as familiarity with technology, the need for immediate recognition, and an expectation for continuous self-development. This article sought to analyze how generation-based career development management can optimize the performance of Generation Z educators. The research employs a qualitative method through interviews, observations, and literature studies. The research findings indicate that Generation Z educators require flexible career paths, technology-based training, and supportive, inclusive workplaces. Additionally, factors such as immediate recognition, constructive feedback, and cross-generational mentoring are crucial in motivating them. The findings also suggest that implementing relevant career development strategies can enhance the productivity of Gen-Z educators while simultaneously improving overall educational quality.ABSTRAKGenerasi Z, yang sering dikenal sebagai "digital natives," semakin banyak yang memilih untuk mengambil profesi sebagai tenaga pendidik. Generasi ini memiliki karakteristik unik, seperti kemampuan adaptif terhadap teknologi, kebutuhan akan pengakuan langsung, dan keinginan untuk pengembangan diri yang berkelanjutan. Artikel ini bertujuan untuk menganalisis bagaimana manajemen pengembangan karir berbasis generasi dapat mengoptimalkan kinerja tenaga pendidik Generasi Z. Penelitian ini menggunakan metode kualitatif melalui wawancara, observasi, dan studi literatur. Hasil penelitian menunjukkan bahwa tenaga pendidik Generasi Z membutuhkan jalur karir yang fleksibel, pelatihan berbasis teknologi, serta dukungan lingkungan kerja yang inklusif. Selain itu, faktor seperti pengakuan langsung, umpan balik konstruktif, dan mentoring lintas generasi menjadi elemen penting untuk memotivasi kinerja mereka. Penerapkan strategi manajemen pengembangan karir yang relevan dapat meningkatkan produktivitas tenaga pendidik Generasi Z sekaligus meningkatkan kualitas pendidikan secara keseluruhan.